The Effect of Training and Motivation on Employee Performance Mediated by Job Satisfaction at The Agriculture Service of Tabanan District - A. A. Sagung Putri Diantari (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2023)
This study aims to analyze education and training and motivation on employee work result which is mediated by job satisfaction at the Livestock Service Office of Tabanan Regency with the 2022 research year involving 64 respondents. This study was conducted by using data collection methods with observation, interviews, documentation, surveys. This study used a saturated sample because the population is less than 100, the results use Partial Least Square (PLS). Based on analysis, the results of this study showed that there is the increase of motivation on job satisfaction, education and training increased on job satisfaction, job satisfaction increased on employee work result. Motivation has a positive but not significant effect on employee work result, education and training has a positive but not significant effect on employee work result, job satisfaction is the perfect mediation, the relationship between education and training on employee work result is not significant, while there is an indirect relationship between education and training and performance employee through significant job satisfaction, perfect job satisfaction mediates the relationship between motivation and employee work result is not significant, while the indirect connection between motivation and employee work result through satisfaction does not increase. The implications of this research for related parties to improve employee work result are affected by training and motivation mediated by job satisfaction.